"The Writer and Poet Taher Tahri: His Life and Works" - marouk, issa (El Omda in Linguistics and Discourse Analysis, 2018)
Algeria is rich in literary and poetic figures who have had a prominent presence in the Algerian and Arab cultural scene. Despite attempts to revive Algeria’s literary heritage, many names remain unexplored, requiring significant effort and research to publish and disseminate their literary and critical works. This is not limited to literary production from earlier periods; it also encompasses the colonial era and what writers produced during that dark chapter of Algeria’s history. Despite the constraints of colonial oppression, a generation of Algerians upheld the banner of the Arabic language and its literature, developing various arts, including poetry and prose. The Association of Algerian Muslim Scholars and the reformist movement played a pivotal role in bringing to prominence several figures in the 1940s and 1950s, among them the writer and poet Taher Tahri.